SOCIAL INDICATORS OF THE USE OF HUMAN RESOURCES IN SUPPORT OF BUSINESS ACTIVITY IN UZBEKISTAN - Alimardonova Gulifzoda Alimardon kizi (American Journals, 2024)
In this article, the development of entrepreneurship must have the necessary resources and have the opportunity to achieve them. Often we can observe a situation where it is almost impossible to get resources due to the demands of the society. This, of course, creates frustration and dissatisfaction among entrepreneurs.
Keywords: human resources, human capital, human potential, labor market, entrepreneurial ability, information resources